Electric field prediction using micro-plasma inside a microwave cavity for soot oxidation - Al-Wakeel, H.B. (EDP Sciences, 2014)
The reduction of the harmful emission soot is necessary in recent years due to the environmental protection regulation. Soot is a carbonaceous matter and a strong absorber of microwave energy. Microwave heating offers the advantage over conventional heating to oxide soot. Where plasma is high electric field that leads to instantaneous temperature rising. This paper proposes a recent concept for soot oxidation using micro-plasma in a microwave cavity. The concept was presented by simulating the electric field using microwave heating and thin metal object. Five cases were examined numerically in a mono-mode TE 10 microwave cavity WR430 having closed surfaces of perfect electric conductors working under 2.45 GHz frequency and 1500 W power supply to predict the electric field and dissipated heat distribution. The methodology of prediction was implemented using ANSYS based on FEM. The present prediction results showed higher electric field (400 kV/m) and high dissipated heat (3.7Ã1010 W/m3) can be obtained for a soot sample backed with metal rods inserted vertically with gaps not exceeding 1.5 mm between the rods tips. Also increasing the number of metal rods, from 8 to 14 increases the maximum value of electric field formed in the soot sample to 575 kV/m. The simulation results revealed the ability of achieving high electric field by using microwave heating with the assistance of metal objects. Â© 2014 Owned by the authors, published by EDP Sciences.